Diversity and inclusion in sport organizations : a multilevel perspective - George B. Cunningham (New York, New York : Routledge, 2019)
Diversity and Inclusion in Sport Organizations: A Multilevel Perspective is a comprehensive introduction to the ways in which people differ -- including race, gender, age, mental and physical ability, appearance, religion, sexual orientation, and social class -- and the importance of these differences for sport organizations. It offers strategies for managing diversity in work and sport environments and provides an overview of diversity training that can be implemented in the workplace. Grounded in research and theory and outlining best practice, this fully updated and revised edition includes more international examples and expanded coverage of topics, such as critical disability studies, women of color, and lesbian, gay, bisexual, transgender, queer, intersex issues, as well as useful teaching and learning features in every chapter and additional online resources. This is important reading for students working in the fields of sport business, sport management, sport development or sport coaching, HR management in sport, sport in society, sport participation, ethical leadership in sport, or introductory sport management courses.
Keywords: Discrimination in sports United States; Sports administration; Diversity in the workplace